(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Modern industry and manufacturing require future metrologists not only deep theoretical knowledge, but also professional and personal skills such as the ability to take independent initiative, solve problems, and work effectively in a team. Therefore, the higher education system is faced with the task of aligning the level of professional training of future specialists with the requirements of the labor market. In Uzbekistan, great attention is also paid to this issue, in particular, the Concept for the Development of the Higher Education System until 2030 was approved by Decree No. PF-5847 of October 8, 2019 [ Error! Reference source not found.]. The next logical stage of our research work will be to study the current state of the problem of the development of the concepts of "metaprodmet competence" and "metaprodmet competence". If we associate the current development of our country with significant changes in the field of technology, industry, mechanical engineering and construction, then it is precisely this aspect that creates a need in our society for a qualified future metrologist engineer who has thoroughly mastered his profession and has certain personal qualities.